State failure in the context of the operations of transnational corporations - Pilarska, Czesława (Zawodność państwa w kontekście działalności korporacji transnarodowych, 2020)
The main purpose of the paper is to discuss issues related to the failure of the state in the context of selected areas of operation of transnational corporations (TNCs). The analysis presented in the paper showed that the state turs out to be ineffective with reference to transnational corporations in many areas of their operation (e.g. tax avoidance by TNCs, the use of their monopolistic position, their negative impact on the natural environment as well as economic sensitivity). The sustainable growth of the global economy requires actions not only in each country but also by international organisations and integrating groupings that could work out certain rules concerning compliance with tax regulations by TNCs and also more effective control over the business of those entities, including control over capital flows on a global scale. The problems discussed in the paper contribute to the main stream of research concerning the role of the state in market economy and the limited effectiveness of the state in exercising control over the operations of transnational corporations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 10, s. 88-106